Management of the Upstream Ciliwung Watershed, Bogor Regency - Edial, Helfia; Fatihah, Anisa; Mardhatillah, Fitria Rahmi; Kausesra, Lastria; Berlian, Muhammad; Fadillah Silalahi, Muhammad Haris; Irfansyah, Muhammad; Rosa, Novia; Nur Salsabila, Tri Raisya (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This report presents the results of research on the management of the Upper Ciliwung River Basin (DAS) in Bogor Regency, which aims to analyze the relationship between upstream area factors and flood events in Jakarta, and provide recommendations for better management. This research was conducted using a qualitative descriptive method through field surveys and literature studies. The results show that the Upper Ciliwung Watershed has diverse physical characteristics, with topography varying from lowlands to steep, and a climate influenced by high rainfall. Land use changes, especially the increase in residential areas, have reduced water absorption capacity and increased surface runoff, which contributes to increased flood risk downstream. In addition, the geological and hydrological conditions of the watershed also affect river flow discharge. Therefore, integrated and sustainable management is needed to maintain ecosystem balance and reduce negative impacts on the environment. Recommendations provided include strengthening land zoning policies, implementing conservation techniques, and increasing community participation in water resource management.